Multi-wavelength properties of X-ray sources in the Chandra/XMM-Newton 13H deep field survey area - Loaring, N.; Page, M.; Dwelly, T.; Seymour, Nick; McHardy, I. (2010)
We present the results of a multi-wavelength analysis of the properties of a sample of 86 X-ray selected AGN. X-ray flux and optical magnitude are strongly correlated in broad-line AGN (BLAGN) as expected from the unified model. Narrow emission line galaxies (NELGs), however, display a wide range in optical brightnesses for a given X-ray flux, which we attribute to varying amounts of obscuration and host galaxy contamination. We find that more luminous AGN and increasingly softer X-ray AGN show redder mid infrared power law slopes in their spectra between 3.6 and 8 µm. The power law slope between 3.6 and 24 µm is however uncorrelated with X-ray luminosity and X-ray spectral index. © 2010 American Institute of Physics.